PARAMETRIC STATISTICS APLICABILITY TO BIO-MEDICAL DATA ANALYSIS - A. N. Gerasimov; M. Yu. Serdyukova (Сеченовский вестник, 2016)
Parametric statistics calculates the statistical signiﬁcance of dirences assuming normality of the random variables in question. Since all random variables used in real biomedical research are not normally distributed, it is necessary to validate parametric statistical methods, i.e. evaluate the errors in the calculation of the statistical signiﬁcance of diﬀerences. Unfortunately this test is performed incorrectly. The article describes the causes of errors in parametric statistics and presents a software program which calculates the error value resulting from the abnormal empirical distribution of the mean from a set of observations.